The influence of alcohol consumption among partners in newly cohabiting relationships. (3rd December 2019) - Leggat, Geoffrey; Livingston, Michael; Kuntsche, Emmanuel; Kuntsche, Sandra; Callinan, Sarah
Abstract: Introduction and Aims: Research has linked exposure to the drinking of one's partner or spouse and changes in alcohol‐related behaviours. However, there is a dearth of studies which consider only cohabiting relationships. More couples are preferring to cohabit prior to and in place of marriage. As a result, studies focused on cohabiting couples may provide a more representative consideration of modern long‐term relationships. The present study uses a representative, longitudinal sample with annual follow‐up and aims to determine if cohabiting partner's drinking habits are influenced by their partner's consumption, as well as consider the role of intimacy as a key component of these influences compared to a relationship's label or legal status. Design and Methods: Data from the Household, Income and Labour Dynamics in Australia survey identified 1483 newly cohabiting, Australian heterosexual couples between 2001 and 2016. Individual alcohol consumption was analysed using a cross‐lagged, three‐wave actor‐partner structural equation model. Results: A respondent's own drinking was a stable and significant predictor of future consumption, and a greater predictor of later drinking than their partner's. Female consumption generally exerted significant influence on their male partner's later consumption, while male drinking was non‐significant for all but the first year following cohabitation. Overall, women generally had greater influence on their partner's drinking than men. Discussion and Conclusions: This study furthers our understanding of each partner's role in influencing consumption within intimate relationships. Cohabiting couples appear to have some similarities with married couples regarding partner influence and may better represent the typical contemporary long‐term relationship.